2018
DOI: 10.5137/1019-5149.jtn.24029-18.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of single lumbar transforaminal epidural steroid injections for the treatment of l4-5 and l5-s1 paramedian disc herniation

Abstract: deficit. Sometimes the pain can be unbearable but the patient does not want surgical intervention. Nerve root compression may stimulate inflammatory processes (14,17), providing a rationale for the use of corticosteroids to inhibit inflammation and alleviate pain. The transforaminal epidural injection of corticosteroids under fluoroscopic guidance delivers high concentrations of therapeutic agents to the site of pathology (5). Appropriately performed transforaminal epidural steroid █ INTRODUCTION R adicular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the study by Ghahreman and Bogduk [37], they concluded that the success of transforaminal epidural corticosteroid application was almost three times greater in patients with lesser nerve root compression. According to Adiley et al [38], the comparison ofthe PRT effects in L4-L5 and L5-S1 on disc herniation showed greater efficiency in L4-L5 levels. The results are also compatible with the study by Shrestha et al [39], where the successful treatment at the L5-S1 level was 57.14% compared to the L4-L5 level of 79.17%.…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Ghahreman and Bogduk [37], they concluded that the success of transforaminal epidural corticosteroid application was almost three times greater in patients with lesser nerve root compression. According to Adiley et al [38], the comparison ofthe PRT effects in L4-L5 and L5-S1 on disc herniation showed greater efficiency in L4-L5 levels. The results are also compatible with the study by Shrestha et al [39], where the successful treatment at the L5-S1 level was 57.14% compared to the L4-L5 level of 79.17%.…”
Section: Discussionmentioning
confidence: 98%
“…Donoszono, że jeden na czterech pacjentów poddanych ESI z powodu przepukliny lub zwężenia kręgosłupa lędźwiowego miał następnie operację, a prawie jeden na sześciu miał operację w ciągu pierwszego roku [22]. Badanie wykazało, że transforaminalne zewnątrzoponowe iniekcje glikokortykosteroidowe w przypadku przepukliny dysku paramedian L4-5 były bardziej skuteczne niż transforaminalne zewnątrzoponowe iniekcje glikokortykosteroidowe w przypadku przepukliny dysku L5-S1 w 12-tygodniowym okresie obserwacji [23].…”
Section: Leczenie Farmakologiczneunclassified
“…The effectiveness of TFESI under fluoroscopy for the alleviation of radicular pain because of the LDH has been demonstrated in different studies (1,2,3,6,9). In individuals with extruded LDH, the mean VASs for radicular pain before and after the procedure were 87.65 ± 5.59 and 22.81 ± 4.01, for each group.…”
mentioning
confidence: 95%